2023
DOI: 10.1039/d2su00102k
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable and efficient production of furoic acid from furfural through amine assisted oxidation with hydrogen peroxide and its implementation for the synthesis of alkyl furoate

Abstract: Aromatic functionality is an important feature for the design of new molecules with specific properties. Today fossil fuel feedstocks provide aryl building blocks with well-known chemistry which can be implemented...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…A technoeconomic assessment of the proposed process indicated that the operating costs associated with the synthesis of the hydrophobic part of the molecule are competitive for producing a low cost surfactant but this will be strictly dependent on the production cost of furoic acid which large scale production is not in place yet. 595,605 Other studies have been reported to produce biobased LAB through cycloaddition of furan with dodecene through but further studies are needed to improve the selectivity and recyclability of the catalyst, in addition to design an efficient process for the decarboxylation of furan. 606 Fig.…”
Section: Synthesis Of Furan Based Surfactantsmentioning
confidence: 99%
See 1 more Smart Citation
“…A technoeconomic assessment of the proposed process indicated that the operating costs associated with the synthesis of the hydrophobic part of the molecule are competitive for producing a low cost surfactant but this will be strictly dependent on the production cost of furoic acid which large scale production is not in place yet. 595,605 Other studies have been reported to produce biobased LAB through cycloaddition of furan with dodecene through but further studies are needed to improve the selectivity and recyclability of the catalyst, in addition to design an efficient process for the decarboxylation of furan. 606 Fig.…”
Section: Synthesis Of Furan Based Surfactantsmentioning
confidence: 99%
“…A technoeconomic assessment of the proposed process indicated that the operating costs associated with the synthesis of the hydrophobic part of the molecule are competitive for producing a low cost surfactant but this will be strictly dependent on the production cost of furoic acid which large scale production is not in place yet. 595,605…”
Section: Furan Based Surfactants As Replacements For Lasmentioning
confidence: 99%
“…Several processes based on the largescale depolymerisation/processing of lignocellulosic biomass for the generation of benzenoid feedstocks have been proposed. [4] However, most of these processes are costly, resource intensive and low-yielding, often producing highly oxygenated aromatics (e. g., vanillin, syringic acid) [5] that are poorly suited as feedstocks for manufacturing aromatic products in existing chemical plants. [6] Monoterpenes are an alternative class of biorenewable whose unsaturated hydrocarbon structures are ideally suited as feedstocks for the industrial syntheses of many sustainable chemical products.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the various conditions studied that can be used to produce furoic acid/their derivatives, those are unfortunately not very conducive to producing these chemicals in large quantities at affordable prices. …”
Section: Introductionmentioning
confidence: 99%